Genome Size, rDNA Copy, and qPCR Assays for Symbiodiniaceae - Saad, Osama S.; Lin, Xin; Ng, Tsz Yan; Li, Ling; Ang, Put; Lin, Senjie (Frontiers in Microbiology, 2020)
Symbiodiniaceae community structure in corals is crucial for understanding the plasticity of different holobionts under environmental stress. While this relies on molecular analyses, accuracy of molecular quantification, as influenced by DNA extraction efficiency and rDNA copy number variations in particular, has rarely been systematically investigated. Here, we report the development of a set of genus-specific qPCR assays. First, a protocol for efficient DNA isolation and accurate measurements of genome size and rDNA copy number was established. Second, seven newly designed genus-specific ITS2 primer sets were validated using computational and empirical analyses and qPCR assays were developed. We find that while the genome size ranges between 1.75 ± 0.21 and 4.5 ± 0.96 Gbp, rDNA copy number shows over tenfold variation among Symbiodiniaceae species. Our protocol produced standard curves with high efficiencies (89.8 to 99.3%; R2 ≥ 0.999) and tight Cq values over different PCR conditions, illustrating high specificity and sensitivity of the qPCR assays. Tested on mock communities of mixed culture species, our qPCR results agreed well with microscopic counts and facilitated calibration of metabarcoding data. To test the applicability of our protocol for field samples, we analyzed three different Hong Kong coral samples. Six Symbiodiniaceae genera were detected in Acropora valida, Oulastrea crispata and Platygra acuta, with Breviolum, Effrenium, Fugacium and Gerakladium sp. being reported for the first time. Our results suggest that aggressively disrupting cells to ensure thorough cell lysis, estimating cell loss and DNA loss, and validating qPCR assays are critical for success. The number of species examined here is limited, but the primers are potentially applicable to most species in respective genera, and the protocol and the approach to develop it provide a base and template towards a standardized procedure for quantitatively characterizing Symbiodiniaceae communities in corals.